IMPLEMENTASI ALGORITMA LEAST SQUARE UNTUK FORECASTING PADA TOKO MABEL - Nurul Fuad; Dedy Aprianto (SPIRIT, 2022)
The people's purchasing power for wood-processed products has increased significantly, especially for home accessories such as doors, windows, tables, chairs, and so on. UD Jatisubur is a business selling various types of furniture. The purpose of this study is to apply the Least Square method to predict the sale of goods at the UD Jatisubur store. Prediction is a guess or estimate about the occurrence of events in the future. Prediction is the ability in a business to expect the purchase and use of a product until the product can be made in the correct quantity. Prediction is the process of estimating future demand. In sales activities, predictions are made to determine the number of sales on a product. In this application the method used is Least Square. The Least Square method is used to calculate the number of sales of goods in the following year, namely 2021. Data on sales of goods during 2016 to 2020 with items such as doors, windows, tables, chairs and cabinets. The results of the prediction of sales of goods in 2021, obtained as many as 103 doors with MAPE 14.247%, windows as many as 93 with MAPE 8.4755%, chairs as many as 21 with MAPE 6.7767%, tables as many as 12 with MAPE 3.8283%, and cupboards as many as 15 with a MAPE of 16.00413%.